Effects of Fatty Acid Metabolites on Adipocytes Britening: Role of Thromboxane A2 - Cécilia Colson; Pierre-Louis Batrow; Sebastian Dieckmann; Laura Contu; Christian H. Roux; Laurence Balas; Claire Vigor; Baptiste Fourmaux; Nadine Gautier; Nathalie Rochet; Nathalie Bernoud-Hubac; Thierry Durand; et al. (Cells, 2023)
Obesity is a complex disease highly related to diet and lifestyle and is associated with low amount of thermogenic adipocytes. Therapeutics that regulate brown adipocyte recruitment and activity represent interesting strategies to fight overweight and associated comorbidities. Recent studies suggest a role for several fatty acids and their metabolites, called lipokines, in the control of thermogenesis. The purpose of this work was to analyze the role of several lipokines in the control of brown/brite adipocyte formation. We used a validated human adipocyte model, human multipotent adipose-derived stem cell model (hMADS). In the absence of rosiglitazone, hMADS cells differentiate into white adipocytes, but convert into brite adipocytes upon rosiglitazone or prostacyclin 2 (PGI2) treatment. Gene expression was quantified using RT-qPCR and protein levels were assessed by Western blotting. We show here that lipokines such as 12,13-diHOME, 12-HEPE, 15dPGJ2 and 15dPGJ3 were not able to induce browning of white hMADS adipocytes. However, both fatty acid esters of hydroxy fatty acids (FAHFAs), 9-PAHPA and 9-PAHSA potentiated brown key marker UCP1 mRNA levels. Interestingly, CTA2, the stable analog of thromboxane A2 (TXA2), but not its inactive metabolite TXB2, inhibited the rosiglitazone and PGI2-induced browning of hMADS adipocytes. These results pinpoint TXA2 as a lipokine inhibiting brown adipocyte formation that is antagonized by PGI2. Our data open new horizons in the development of potential therapies based on the control of thromboxane A2/prostacyclin balance to combat obesity and associated metabolic disorders.